The Effectiveness of using the Project-Based Learning Module Viewed From The SEPs Skills of Students - Amalia, Yushinta (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
This study is intended to determine the effectiveness of using the project-based learning module viewed from the Science and Engineering Practices (SEPs) skills of students. The study employs a one-group pretest-posttest design involving 35 students of SMAN (State Senior High School) 1 Andong. There were six aspects of SEPs use in this study: asking questions and defining problems (SEP-1), developing and using models (SEP-2), planning and carrying out investigations (SEP-3), analyzing and interpreting data (SEP-4), constructing explanations and designing solutions (SEP-6), and Obtaining, evaluating and communicating information (SEP-8). The question instrument in this study was 13 two-tier multiple-choice (TTMC) test items developed corresponding to the science and Engineering Practices skills indicators in California Science Test Practices. The results of the study uncovered that the N-Gain value was 0.52, which means that the increase in the students’ SEPs skills was in the medium category. The enhancement of each aspect of SEPs N-Gain was SEP-1: 0.54; SEP-2; 0.54; SEP-3: 0.49; SEP-4: 0.51; SEP-6: 0.53; and SEP-8: 0.56.